Pengadaan Bahan Baku Produk Kopi Ready to Drink pada Coffee Shop di Kota Bandar Lampung - Annisa Fitri; Dayang Berliana; Nuni Anggraini (AGRIMOR, 2021)
Coffee shops are currently still constrained by the procurement of raw materials, assurance of product quality continuity, inadequate supply, and the accuracy of delivery time. This study aims to understand the characteristics of coffee entrepreneurs and the accuracy of the procurement of coffee shop coffee raw materials in Bandar Lampung. This research was conducted from May to October 2020. Sampling has done by snowball technique for 10 coffee shops. The data analysis method used is descriptive qualitative method. The results showed that coffee shop entrepreneurs in Bandar Lampung are coffee shop entrepreneurs aged 20-29 years, have a higher education level, had experience less than two years, and coffee shop entrepreneurs have of 6 workers in average. Procurement of raw materials has met the criteria for the accuracy of timing and quantity. However, it is necessary to increase the accuracy of the place, price, type, quantity, and quality, so that the sustainability of the coffee shop business in Bandar Lampung can be maintained.